Over a million students use our free study notes to help them with their homework
First, expand (x-2)2:
= (x-2)(x-2),
= x2 - 2x - 2x + 4
= x2 - 4x + 4
Add on the +7:
= x2 - 4x + 11
<...
As we know, to find a gradient in a linear function, we have to calculate the difference in the objective function (usually y) by the difference in the choice variable (commonly x), you may know this as r...
A) 6n - 12
B) p(p-5)
y-y1=m(x-x1)
y-4=1.5(x-2)
y-4=1.5x-3
y=1.5x+1
First find the nth term of the sequence. Start by finding the difference between each term:
3, 5, 7, 9, 11 - the difference between each is 2 therefore it is 2n but this alone gives the sequence: 2...
←
645
646
647
648
649
→
Internet Safety
Payment Security
Cyber
Essentials